The Influence Of Brand Ambassadors, Instagram Promotions On Purchasing Decisions In Cirebon - M. Badruddin; Jannathan Syahru Sudarso; Muhammad Santoso; Rahmadi Rahmadi (CV. AFDIFAL MAJU BERKAH, 2025)
In the digital era, social media platforms such as Instagram have become an important tool for marketing and customer engagement. This research investigates the impact of Brand Ambassador and Instagram Promotion on consumer purchase choices, especially on Skintific skin care products in Cirebon. The purpose of this study is to determine the result of Brand Ambassador and Instagram Promotion on Purchasing Decisions in Cirebon. The study's respondents were Skintific user consumers throughout Cirebon. With a sample of 111 respondents, this study used a quantitative approach by distributing online questionnaires and analyzing the data using multiple linear regression in the SPSS (Statistical Package for the Social Sciences) application. The validity and reliability tests showed high internal consistency, with Cronbach’s Alpha values of 0.946 (Brand Ambassador), 0.950 (Instagram Promotion), and 0.929 (Purchase Decision). The results showed that both Brand Ambassador and Instagram Promotion significantly influenced purchasing decisions (R² = 0.919), with Instagram promotion having a stronger influence (β = 0.828) than brand ambassadors (β = 0.185). The regression model demonstrates that 91.9% of the variation in purchasing decisions can be clarified by these two variables. This study found that digital marketing strategies, especially those that leverage social media engagement, play an important role in shaping consumer behavior. Companies are advised to optimize Instagram-based promotions while maintaining more effective use of Brand Ambassadors to improve brand image and sales performance.